Synthesis, polymerisation and characterisation of a novel olefin-modified acrylate monomer, 1-methyl-1-propyl-hexel acrylate - Mange, Siyabonga (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.